Deconstructing The Concept of “Green Deen” By Abdul Martin and Its Implementation for Boarding Schools in The City of Kediri - Solichin, Moh. Badrus; Bahtiar, Moh. David (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The root of problem of this research begins with nature of humans who are positioned as caliphs on earth, and are mandated to maintain sustainability and not act antropocentrically towards nature and its ecosystem. Then researchers discovered the fact that from students in Islamic boarding schools movement could be created to protect and preserve natural ecosystems, as well as behaving in a friendly manner towards the environment according to the teachings of the Islamic religion. Through this research the author will examine this issue by deconstructing Abdul Matin's